The role of social capital as a mediator of the effectiveness of counseling on innovative behavior in increasing corn farmers' income in Bone Bolango Regency - Saleh, Yanti; Boekoesoe, Yuriko; Wibowo, Larasati Sukmadewi; R, St. Aisyah; Tolinggi, Wawan K.; Hippy, Mohammad Zubair (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Corn farming faces various challenges from economic, ecological, and institutional aspects. For effective agricultural extension, it is crucial to optimize the role of social capital, which catalyzes optimizing corn farming, particularly concerning the extent to which farmers become innovative in increasing income. Methods: This research employed a quantitative approach. The data were collected through primary sources via the distribution of questionnaires to 175 farmers as per sampling requirements, as well as interviews and field observations. Data analysis techniques included descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: (1) The effectiveness of extension services significantly and positively influences corn farmers' social capital, with a coefficient value of 43.00%. (2) The effectiveness of extension services significantly and positively affects innovative behavior in increasing income among corn farmers, with a coefficient value of 22.80%. (3) Social capital significantly and positively influences innovative behavior in increasing income among corn farmers, with a coefficient value of 74.80%. (4) The effectiveness of extension services through social capital significantly and positively influences innovative behavior in increasing income among corn farmers, with a coefficient value of 32.20%, resulting in a total effect of 55.00%. Conclusion: Social capital serves as a significant intervening factor, as its enhancement facilitates agricultural extension workers in their tasks by encouraging farmers to become more innovative in increasing both production and income from corn farming in the Bone Bolango Regency.